The use of certain elements of the marketing communications system by Ukrainian pharmacies in emergencies - Demchenko, V. O.; Demchenko, V. O.; Tkachenko, N. O.; Mahanova, T. V.; Демченко, Валерій Олегович; Демченко, Вікторія Олександрівна; Ткаченко, Наталя Олександрівна; Маганова, Тамара Валеріївна (My University, 2024)
The purpose of the study was to determine the degree of influence of the marketing communications system elements on consumer preferences for pharmaceutical products and the loyalty of drug consumers to pharmacies in the conditions of martial law, with further recommendations for the management of pharmacies in wartime. The results of the study showed that the patient’s choice of a pharmacy to receive pharmaceutical care is largely influenced by the following factors: convenient location of the pharmacy to the place of residence; affordable prices for the necessary medicines and the level of physical availability of medicines that meets all the patient’s needs. Among the sources of information that influence the choice of drugs, 75% of respondents indicated recommendations or prescriptions of a doctor, recommendations of a pharmacist – 46.7%, 9.8% – advertising products. Queues, unprofessional care and the pharmacist’s intrusive manner of communication are the factors that cause the greatest negative emotions. In the conditions of martial law, people pay attention to advertising, which helps to orientate on the necessary pharmaceutical products, as well as assess their economic availability at a specific moment in time. Therefore, pharmacy management needs to focus attention and resources on building clear communication links with patients using informational and reference digital technologies.
Keywords: pharmaceutical care; pharmaceutical services; emergencies